Pertanggungjawaban Terhadap Tindak Pidana Perikanan Menurut Undang-Undang Nomor 45 Tahun 2009 Tentang Perikanan - Annisa Yuni Ashri; Bunga Sulastriani; Retno Wahyudi; Amallinda Agustin; Anneke Wulandar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
If the fishing sector is well managed and expert, the volume of exports can increase. It will increase the country's income so that the country can the goal of creating a just and prosperous society. The use of materials or tools that may jeopardize the sustainability of fish resources or the environment that exists around fish habitats falls within the category of fishing offences regulated in the Fisheries Act No. 45 of 2009. Victims affected by corporate action in the field of fishing are expected to get help from the use of repressive and restorative techniques. The restoration of traditional fishermen in such conditions will allow the fisherman to return to a decent life.